Seven new Otacilia Thorell, 1897 species from China (Araneae: Phrurolithidae) - Mu, Yannan; Zhang, Feng (Zootaxa, 2021)
Seven new species of Otacilia Thorell, 1897 from China are described and illustrated, all from both sexes: O. ensifera sp. nov. and O. arcuata sp. nov. from Hunan Province; O. spiralis sp. nov. from Hunan Province and Chongqing City; O. lubrica sp. nov. and O. wuli sp. nov. from Chongqing City; O. dentigera sp. nov. from Sichuan Province; and O. shanxi sp. nov. from Shanxi Province. Based on Jin et al. (2016), the seven new species described here belong to two species groups: O. ensifera sp. nov., O. shanxi sp. nov., O. spiralis sp. nov. and O. lubrica sp. nov. belong to the armatissima-group, while O. wuli sp. nov., O. dentigera sp. nov. and O. arcuata sp. nov. belong to the longituba-group.